Droplets As Liquid Robots - Čejková, Jitka; Banno, Taisuke; Hanczyc, Martin M; Štěpánek, František (Artificial life, 2017)
Liquid droplets are very simple objects present in our everyday life. They are extremely important for many natural phenomena as well as for a broad variety of industrial processes. The conventional research areas in which the droplets are studied include physical chemistry, fluid mechanics, chemical engineering, materials science, and micro- and nanotechnology. Typical studies include phenomena such as condensation and droplet formation, evaporation of droplets, or wetting of surfaces. The present article reviews the recent literature that employs droplets as animated soft matter. It is argued that droplets can be considered as liquid robots possessing some characteristics of living systems, and such properties can be applied to unconventional computing through maze solving or operation in logic gates. In particular, the lifelike properties and behavior of liquid robots, namely (i) movement, (ii) self-division, and (iii) group dynamics, will be discussed.
Keywords: materiálová věda; mikrotechnologie; fyzikální chemie; chemické inženýrství; Microtechnology; smáčivost; Materials Science; Movement; Robotics; pohyb; nanotechnologie; Nanotechnology; Wettability; Hydrodynamics; Chemical Engineering; hydrodynamika; Chemistry, Physical; robotika